Aktivitas Ekstrak Daun Jarak Kepyar (Ricinus communis Linnaeus) terhadap Perkembangan Nematoda Meloidogyne spp. pada Tanaman Tomat (Lycopersicum esculentum Miller) - Elisa Oktavia; Winarto Winarto; Eri Sulyanti (Plant Protection Departement, Faculty of Agriculture, Universitas Andalas, 2021)
Meloidogyne spp. is one of the nematodes that cause root-knot on tomato plants. The botanical nematicide that potentially suppresses the nematode is castor bean leaves (Ricinus communis Linnaeus) extract. This research aimed to get the lethal concentration (LC50 and LC95) of castor bean leaves extract against nematode larvae in-vitro and their effect on the development of root-knot nematode (Meloidogyne spp.) in-planta on tomato plant. The research was carried out in Plant Pest and Disease Laboratory and Greenhouse of Agriculture Faculty, Universitas Andalas, using a completely randomized design (CRD) with two stages; in-vitro and in-planta. The research was used the experiment method in-vitro testing consists of six treatments and five replications, and in-planta testing consists of three treatments and nine replications. The result showed that the application of castor bean leaves extracts invitro can suppress Meloidogyne spp. larvae with LC50 by 0,27% and LC95 by 0,87%. The application of castor bean leaves extract in-planta with treatment concentration 2xLC95 (1,74%) showed effectiveness by 74,69% against the developments of Meloidogyne spp. on tomato plant roots.